Impact of Economic and Trade Expansion of China on Employment and Household Welfare in Burkina Faso: A Computable General Equilibrium Analysis - Sawadogo, Boureima; Nana, Tégawendé Juliette; Natama, Maimouna Hama; Bama, Fidèle; Tapsoba, Emma; Zerbo, Kassoum (International Journal of Economics and Financial Issues, 2020)
The impact of economic and trade expansion of China on Burkina Faso’s economy is analyzed in this work through three channels: trade in goods and services, foreign direct investment and development assistance. To capture the direct and indirect effects of Chinese growth, we use a computable general equilibrium model. The results show that expanded trade with China leads to an increase in domestic prices, an increase in exports to China among product categories for which exports increases, and an increase in imports. The effect on growth, value added ad household wellbeing is small. We find a decline in domestic prices, an increase in exports and a decline in imports. Higher FDI inflows induce additional economic growth equal, increased total labour demand and increased average household well-being, especially among cotton farmers. Keywords: FDI, Aid, trade, CGE, Chine, Burkina Faso JEL Classifications: F14, F35, D58, O19 DOI: https://doi.org/10.32479/ijefi.10699